Millets can have a major impact on improving iron status, hemoglobin level, and in reducing iron deficiency anemia: A systematic review and meta-analysis - Anitha, Seetha; Kane-Potaka, Joanna; Botha, Rosemary; Givens, D. Ian; Sulaiman, Nur Liana Binti (Frontiers Media, 2021)
The prevalence of iron deficiency anemia is highest among low and middle-income countries. Millets, including sorghum, are a traditional staple in many of these countries and are known to be rich in iron. However, a wide variation in the iron composition of millets has been reported, which needs to be understood in consonance with its bioavailability and roles in reducing anemia. This systematic review and meta-analysis were carried out to analyze the scientific evidence on the bioavailability of iron in different types of millets, processing, and the impact of millet-based food on iron status and anemia. The results indicated that iron levels in the millets used to study iron bioavailability (both in vivo and in vitro) and efficacy varied with the type and variety from 2 mg/100 g to 8 mg/100 g. However, not all the efficacy studies indicated the iron levels in the millets. There were 30 research studies, including 22 human interventions and 8 in vitro studies, included in the meta-analysis which all discussed various outcomes such as hemoglobin level, serum ferritin level, and absorbed iron. The studies included finger millet, pearl millet, teff and sorghum, or a mixture of millets. The results of 19 studies conducted on anaemic individuals showed that there was a significant (p < 0.01) increase in hemoglobin levels by 13.2% following regular consumption (21 days to 4.5 years) of millets either as a meal or drink compared with regular diets where there was only 2.7% increase. Seven studies on adolescents showed increases in hemoglobin levels from 10.8 ± 1.4 (moderate anemia) to 12.2 ± 1.5 g/dl (normal). Two studies conducted on humans demonstrated that consumption of a pearl millet-based meal significantly increased the bioavailable iron (p < 0.01), with the percentage of bioavailability being 7.5 ± 1.6, and provided bioavailable iron of 1 ± 0.4 mg. Four studies conducted on humans showed significant increases in ferritin level (p < 0.05) up to 54.7%. Eight in-vitro studies showed that traditional processing methods such as fermentation and germination can improve bioavailable iron significantly (p < 0.01) by 3.4 and 2.2 times and contributed to 143 and 95% of the physiological requirement of women, respectively. Overall, this study showed that millets can reduce iron deficiency anemia.